Inter-hospital transfer of referred trauma patients admitted to the trauma centre of King George Medical University - Verma, Vikas; Singh, Arpit; Shantanu, Kumar; Sharma, Vineet (International Journal of Research in Medical Sciences, 2019)
Background: Inter-hospital transfer is a common in trauma victims due to paucity of super-specialty care, lack of specialty beds, and lack of funding. The government of Uttar Pradesh introduced Emergency Medical Response system (EMRS). There is a need to audit and evaluate the transfer process since the introduction of the service. The objectives of this study were to identify critical gaps in the transfer of trauma patients and secondary over triage to the trauma centre of KGMU. Methods: This prospective observational study was conducted on trauma victims referred to the trauma centre. Patients were evaluated for clinical status, Injury Severity Score, protective patient devices present, type of intravenous fluid infusion, mode of transport, and level of referring hospital. Transfer records, transport vehicles and accompanying personal were evaluated. Results: Of the 342 patients enrolled in the study, 91 had a GCS score <8 and 112(32.74%) had a diastolic BP <60 mm Hg at arrival. Twenty patients (5.8%) were referred from tertiary care centers, 74(21.6%) were referred from district hospitals, 136(39.76%) were referred from primary care centers and 112(32.74%) were referred from private hospitals. Date and time of injury was not recorded in any of the patients. Referral time was recorded in 48(14.03%) patients. One hundred seventy-six patients (51.14%) were transferred in EMRS ambulances, 102(29.82%) patients met the criteria for secondary over triage. Conclusions: There is a need to adopt and strictly implement guidelines for transfer of trauma victims to plug the critical gaps in the transfer process.